PTU-143 Quickview in capsule endoscopy: is it enough?. (28th May 2012) - Smirnidis, A; Koulaouzidis, A; Douglas, S; Plevris, J N
Abstract : Introduction: Analysis of small-bowel capsule endoscopy (SBCE) is time consuming. QuickView (QV) has been added to the RAPID ® software to reduce reading times. Its validity though has been questioned. 1 2 We have recently showed that Blue Mode (BM) application provided image improvement for different lesion categories. 3 Aim: To assess the validity of QV with white light (QVWL) and QV with BM (QVBM) reading mode, in patients with obscure gastrointestinal bleed (OGIB), compared with the standard (reference) viewing. Methods: Retrospective study; all SBCE for OGIB (August 2008–November 2011), performed with PillCam ® SB, with complete small-bowel visualisation were included. A clinician with SBCE experience (>200), unaware of the capsule endoscopy reports, reviewed prospectively the SBCE video streams on RAPID ® (ver. 7) platform using QVWL and QVBM. All SBCE were previously reported using standard viewing mode; these reports were taken as reference. Findings were labelled as P0 (non-pathological), P1 (low/indermediate) and P2 (high bleeding potential) lesions. Sensitivity, specificity, negative and positive predictive value (NPV and PPV) for QVWL and QVBM, as compared to reference review, for clinically significant (P1/P2) lesions was calculated. Results: A total of 106 SBCE were analysed. Indications were: overt OGIB in 21 and occult OGIB/IDA in 85. With QVWL, 54 [P0 (28), P1 (18), P2 (8)] lesions were detected; 63 [P0 (48), P1 (13), P2 (2)] with QVBM, as compared to 98 [P0 (67), P1 (23), P2 (8)] by standard (reference) reporting. For P1+P2 lesions, the sensitivity, specificity, PPV and NPV for QVWL (as compared to reference reporting) was 92.3, 96.3, 96 and 92.8%, respectively. For QVBM, the above values were 91, 96, 96.2 and 90.6%, respectively. The mean evaluation time (including reading and time to mark thumbnails) was 443 and 433 sec for QVWL and QVBM, respectively. Conclusion: When urgent SBCE analysis is necessary, for further immediate management planning, the QV mode can be trusted to provide an accurate (almost on-the-spot) diagnosis in most cases. In this setting, BM does not confer any additional advantage over WL. QV has high PPV (all P2 lesions were detected), but the NPV was just above 90% which indicated that QV can miss certain lesions (P1) thus necessitating further capsule review using the standard mode of SBCE. Competing interests: None declared. References: 1. Günther U, Daum S, Zeitz M, et al. Capsule endoscopy: comparison of two different reading modes. Int J Colorectal Dis 2011. 2. Shiotani A, Honda K, Kawakami M, et al. Evaluation of RAPID(®) 5 Access software for examination of capsule endoscopies and reading of the capsule by an endoscopy nurse. J Gastroenterol 2011;46 :138–42. 3. Krystallis C, Koulaouzidis A, Douglas S, et al. Chromoendoscopy in small bowel capsule endoscopy: Blue mode or Fuji Intelligent Colour Enhancement? Dig Liver Dis 2011;43 :953–7.